Cosmologia com interação no setor escuro do Universo. - Marttens, Rodrigo Fernando Lugon Cornejo von (2017)
According to our understanding of the universe, dark matter and dark energy are the dominant components in the dynamics of the current universe, while baryons and radiation contribute only a small fraction of less than 5 % of the cosmic energy. Although this dark sector is important to describe a series of phenomena that are currently observed, its nature is still one of the greatest mysteries of cosmology. In this work we consider the study of models that, unlike the standard model, present a non-gravitational interaction between dark matter and dark energy. Initially, this interaction is parameterized in a general way that depends on an arbitrary function of the ratio between the energy densities of dark matter and dark energy. It is possible to show that in cases where this ratio depends exclusively on the scale factor, this model can be identified with a unified description of the dark sector. Since this general parameterization has no analytical solution, some specific cases of this class of models are chosen to perform a statistical analysis of parameter selection. This statistical analysis is done using the CLASS cosmological code (modified for each model) combined with the statistical code MontePython. This observational test is done by analyzing the data of H0, SNe Ia (JLA) and Planck TT. The purpose of this analysis is to verify how each observational datasets constraints an interaction in the dark sector in counterpart of the ?CDM model, and if there is a concordance between the background results (H0, SNe Ia and BAO) and the results at the linear level (Planck TT).